Estimasi Jumlah Stok Karbon Yang Tersimpan di Lahan Basah Desa Sungai Tohor Kecamatan Tebing Tinggi Timur Kabupaten Kepulauan Meranti Provinsi Riau - Maizaldi, Maizaldi; Amin, Bintal; Samiaji, Joko (Dinamika Lingkungan Indonesia, 2019)
The research was conducted from July to December 2018 which aims to estimate the amount of carbon stock storage in wetland ecosystems that cover the near shore (mangrove) to upper land (peatland) in Sungai Tohor Village. Survey method was applied and sampling was done by non-destructive method that is without harvesting, so as not to change the ecological function of the forest. Data of carbon pool biomass was analysed and calculated in laboratory with allometric equations to extrapolate biomass. The results showed that the total carbon stock storage in the wetland ecosystem that covered the mangrove area to the peat area was equal to 51499.10 tons C / ha and was able to absorb CO2 by 70901.78 tons CO2/ ha. The largest total carbon deposits are in the mangrove region which is equal to 31525.83 tons C/ha, while the peat region has the ability to store lower carbon with a total value of 19973.27 tons C/ha.